2012
DOI: 10.1634/theoncologist.2012-0060
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Therapeutic Approach to Colorectal Cancer in Young and Elderly Patients

Abstract: After completing this course, the reader will be able to:1. Use patient age as only one consideration, along with tumor status and comorbidities, in deciding on treatment strategies for elderly colorectal cancer patients.2. Obtain and apply information regarding the medical, functional, mental, and social status of colorectal cancer elderly patients in order to make appropriate therapeutic decisions.This article is available for continuing medical education credit at CME.TheOncologist.com. CME CME ABSTRACTPurp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 67 publications
5
39
0
1
Order By: Relevance
“…The geriatric CRC population is a very heterogeneous group, including pati ents with excellent health status and others with comorbid conditions, functional dependency, and limited life expectancy [8]. These issues could account for the fact that a significant proportion of elderly CRC patients is undertreated in comparison with younger patients [9][10][11]. Clinicians frequently have to decide whether major surgery is justified in elderly patients with a limited life expectancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geriatric CRC population is a very heterogeneous group, including pati ents with excellent health status and others with comorbid conditions, functional dependency, and limited life expectancy [8]. These issues could account for the fact that a significant proportion of elderly CRC patients is undertreated in comparison with younger patients [9][10][11]. Clinicians frequently have to decide whether major surgery is justified in elderly patients with a limited life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians frequently have to decide whether major surgery is justified in elderly patients with a limited life expectancy. Effectiveness of surgery in elderly patients depends on whether it is done safely, allowing patients to return to productive lives, with a postoperative life expectancy that is improved by the surgical procedure [11]. Although improvements in surgical techniques, anaesthetic procedures, and postoperative care have all made surgery less hazardous, few elderly patients undergo resection for colorectal cancer in comparison with their younger counterparts [12].…”
Section: Discussionmentioning
confidence: 99%
“…Published results for tumours pathological characteristics are conflicting: some studies show more advanced stages in old patients [6] whereas others do not [13].…”
Section: Resultsmentioning
confidence: 97%
“…By contrast, a recent retrospective study showed that young patients with non-metastatic colorectal cancer after surgery had better long-term survival (21). This may in part be due to their good performance status and suitability for chemotherapy (24)(25)(26).…”
Section: Discussionmentioning
confidence: 95%